Inhibitory Test of Bacillus sp. against Phytophthora palmivora Causes Cocoa Fruit Rot Disease - Devi Tria Anjarsari; Endang Triwahyu Prasetyawati; Yenny Wuryandari (Future Science, 2021)
Fruit rot is one of the important diseases in cocoa fruit, which is caused by Phytophthora palmivora. Farmers often control these pathogen using chemical pesticides. However, this method has a detrimental impact on the environment and health. More environmentally friendly fruit rot disease control can use biocontrol agency. Bacillus sp. is one of the biocontrol agents that is able to produce antibiotics that can inhibit the growth of pathogens, especially soil-borne pathogens and have the ability to colonize plant roots. The purpose of this study is to determine the potential of Bacillus sp. in inhibiting the growth of the pathogenic fungus Phytophthora palmivora in vitro. This study used two experimental factors, type of isolates Bacillus sp. Ba-6 isolate, Ba-9 isolate, Ba-12 isolate, Ba-15 isolate, and Ba-17 isolate and the concentration of Bacillus sp. (106 cfu/ml and 109 cfu/ml). The parameters observed were the inhibitory power and the mechanism of inhibition of Bacillus sp. against Phytophthora palmivora. The results of the best in vitro inhibition test on Ba12K2 treatment with an inhibition of 61% with an inhibitory mechanism, namely antibiosis, as evidenced by the presence of zones of inhibition and swelling of the hyphae.